Periodontal healing after nonsurgical therapy with a new ultrasonic device: a randomized controlled clinical trial - M. Christgau (Blackwell Synergy, 2007)
Aim: The aim of this study was to compare the clinical and microbiological healing outcomes following non-surgical periodontal therapy using the new Vectort ultrasonic system versus scaling and root planing (S/RP) with Gracey curettes. Material and Methods: The study comprised 20 chronic periodontitis patients. Using a split-mouth design, both treatment modalities were randomly applied to one quadrant of the upper and the lower jaws each. Clinical and microbiological parameters were assessed at baseline, 4 weeks, and 6 months after treatment. Furthermore, postoperative hypersensitivity was assessed. The Wilcoxon signed rank test (a50.05) was used for statistical analysis. Results: Both therapies provided statistically significant clinical and microbiological improvements of periodontal conditions after 4 weeks and 6 months. Hypersensitive teeth were found only 4 weeks after S/RP. Besides a significantly better bleeding on probing reduction in deep S/RP sites, no other clinical and microbiological parameters revealed significant differences between the sites treated with the Vectort system or S/RP. Conclusion: Both the Vectort system and S/RP provided favourable periodontal healing results, although in deep pockets S/RP appeared to achieve a better resolution of inflammation.